The effect of an unconditional government income transfer on the labour supply of lowincome workers - Kourtney Koebel; Dionne Pohler (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
We use administrative tax data to estimate the effect of the Working Income Tax Benefit (WITB) on the labour supply of single, low-income workers in Canada. Our analytical approach exploits low knowledge of the program, which has two important implications for our research design and identification strategy. First, low program knowledge allows us to treat WITB as an unconditional income transfer. Second, it generates variation in benefit receipt both between and within eligible tax filers over time. We find that benefit receipt has a robust positive effect on employment for single low-income workers, suggesting the additional income helps workers remain attached to the labour market. We also find that WITB receipt reduces labour supply at the intensive margin of work. The positive extensive margin and negative intensive margin results are consistent with a labour-leisure choice model that incorporates the fixed costs associated with working.
Keywords: 330